2019
DOI: 10.1177/0960327119895549
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-182-5p attenuates pulmonary fibrosis via TGF-β/Smad pathway

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung disease with high morbidity and mortality. miR-182-5p is overexpressed in several fibrosis-related diseases but its effect in pulmonary fibrosis has not been reported yet. To investigate the function of miR-182-5p in pulmonary fibrosis, we established bleomycin (BLM)-induced fibrotic mice model and transforming growth factor-β1 (TGF-β1)-treated human embryonic lung fibroblasts model. In this study, miR-182-5p was highly expressed in pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…However, in fibroblasts, the expression of miR-29 was negatively regulated by TGF-β1/Smad3 signal (43)(44)(45). Similarly, Smad7, a negative regulator of TGF-β1, is suppressed by miR-182-5p which is induced by TGF-β1, resulting in the development of IPF (46). TGF-β1 activates Semaphorin (SEMA) 7A and its receptors through a Smad3-independent and Smad 2/3-independent mechanism, respectively, promoting pulmonary fibrosis (47) Activating transcription factor 4 (ATF4) was a pivotal transcriptional regulator for the metabolism of amino acid (48).…”
Section: Tgf-β1: Gentlemanly Orchestrator In Idiopathic Pulmonary Fibrosis (Review)mentioning
confidence: 99%
“…However, in fibroblasts, the expression of miR-29 was negatively regulated by TGF-β1/Smad3 signal (43)(44)(45). Similarly, Smad7, a negative regulator of TGF-β1, is suppressed by miR-182-5p which is induced by TGF-β1, resulting in the development of IPF (46). TGF-β1 activates Semaphorin (SEMA) 7A and its receptors through a Smad3-independent and Smad 2/3-independent mechanism, respectively, promoting pulmonary fibrosis (47) Activating transcription factor 4 (ATF4) was a pivotal transcriptional regulator for the metabolism of amino acid (48).…”
Section: Tgf-β1: Gentlemanly Orchestrator In Idiopathic Pulmonary Fibrosis (Review)mentioning
confidence: 99%
“…miRNAs, a class of noncoding small RNAs, are involved in RNA silencing, posttranscriptional regulation, and other biological processes [ 20 ]. It has been confirmed that miRNAs play a critical role in the occurrence and development of various diseases, including IPF [ 21 23 ]. As an example, miR-92, miR-210, and miR-let-7d have been confirmed to be associated with IPF [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are endogenous, small non-coding RNA that modulate genes at the post-transcription level in various physiological and pathological processes (20). Increasing evidence has indicated that miRNAs drive the onset and progression of PF (21,22).…”
Section: Discussionmentioning
confidence: 99%